Design and experiment of seed furrow cleaning device based on throwing and sliding for no-till maize seeding - Yuan, Panpan; Li, Hongwen; Lu, Caiyun; Wang, Qingjie; He, Jin; Huang, Shenghai; Cui, Dandan (International Journal of Agricultural and Biological Engineering, 2022)
In order to solve the serious problems of seeds are covered by residual film and overhead by straw during no-till seeding, a seed furrow cleaning device for no-till maize seeding was developed, which adopted a collaborative cleaning method of rotating spring teeth and curved sliding shovel. The movement process and motion trajectory of throwing residual film and straw were constructed. The maximum distance of throwing to one side in horizontal and maximum height in vertical were obtained. The motion trajectory of adjacent spring teeth was analyzed by Matlab, the motion trajectories of adjacent spring teeth at different speeds of 120 r/min, 150 r/min and 180 r/min were achieved, the theoretical analysis results showed that the area of omitted area decreased with the increase of rotation speed. Based on theoretical and simulation analysis of critical parameters, the forward speed of machine, rotation speed of spring teeth, and dip angle between spring teeth and rotary disc were selected as the influencing factor. Straw cleaning rate (SCR) and residual film cleaning rate (RFCR) were selected as the response values for three factors and three levels of orthogonal experiment design. The optimal combination of the selected parameters was obtained, and the field test verification was also conducted. The results showed that the rotation speed of spring teeth, forward speed and dip angle of spring teeth significantly affect SCR and RFCR were in decreasing order. The field test results indicated that when forward speed was 6 km/h, rotation speed of spring teeth was 180 r/min and dip angle of spring teeth was 40°, SCR and RFCR were 88.27% and 84.31%, respectively. This study provides a reference for the development of no-till seeder in Xinjiang and the northwestern regions of China.Keywords: maize, conservation tillage, no-till seeding, seed furrow cleaning, straw, residual filmDOI: 10.25165/j.ijabe.20221504.7097Citation: Yuan P P, Li H W, Lu C Y, Wang Q J, He J, Huang S H, et al. Design and experiment of seed furrow cleaning device based on throwing and sliding for no-till maize seeding. Int J Agric & Biol Eng, 2022; 15(4): 95–102.